1988
DOI: 10.1007/bf00314240
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia with recovery related to central pontine myelinolysis

Abstract: Development of severe ataxia and mild pyramidal signs without mental deterioration, tetraparesis or pseudobulbar palsy during recovery from withdrawal delirium and initial hyponatraemia are unusual clinical features consistent with central pontine myelinolysis. This diagnosis was confirmed by magnetic resonance imaging (MRI) in an alcoholic man. Clinical and electrodiagnostic improvement occurred, whereas the MRI findings remained unchanged in a follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Although truncal ataxia is not considered a characteristic feature of CPM, our findings suggest that truncal ataxia in alcoholics indicates the possibility of recent CPM. In fact, CPM accom- panied by cerebellar or sensory ataxia have been reported [4,6,8,11,16,22,27,31]. In contrast, none of our patients had the spastic paraparesis thought to be characteristic of CPM.…”
Section: Discussioncontrasting
confidence: 77%
“…Although truncal ataxia is not considered a characteristic feature of CPM, our findings suggest that truncal ataxia in alcoholics indicates the possibility of recent CPM. In fact, CPM accom- panied by cerebellar or sensory ataxia have been reported [4,6,8,11,16,22,27,31]. In contrast, none of our patients had the spastic paraparesis thought to be characteristic of CPM.…”
Section: Discussioncontrasting
confidence: 77%
“…Misra et al [1] reported two such patients with resolution of ataxia with correction of hyponatremia in 3 days and both of them had volume depletion as cause of hyponatremia. [6,7] In our patient, the cerebellar ataxia is most likely due to hyponatremia and it is possible that the cerebellar atrophy present premorbidly might have contributed to the clinical presentation. However, in both these case reports, MRI brain was not available but ataxia improved within a period of 3 to 7 days which is unlikely with CPM.…”
Section: Reversible Cerebellar Ataxia: a Rare Presentation Of Depletimentioning
confidence: 75%
“…15 Well-documented reports describing a cerebellar syndrome as a presenting feature of CPM are rare. 16 Although our patient had preexisting atrophy of the vermis secondary to alcohol abuse, this was most likely an incidental finding because he had no prior symptoms, and acute dysarthria and appendicular ataxia are not features of degeneration of the vermis, which usually presents with chronic progressive gait ataxia.…”
Section: Discussionmentioning
confidence: 94%